Equine cutaneous habronemosis in a pregnant mare – case report (Research, Society and Development, 2024)
Cutaneous habronemiasis is a disease that affects the skin of horses through the deposition of Habronema spp larvae. The wounds have granulomatous characteristics and are difficult to heal. Treatment can be carried out through surgical removal of the affected tissue and with dewormers to control the vectors, the study in question addresses a non-surgical alternative using copper sulfate as a form of wound debridement. This article aimed to present a case report of equine habronemiasis in a pregnant mare. The animal was treated at a specialized equine clinic in the city of Cacoal/RO, and showed no significant changes on clinical examination, with only ulcerative wounds being observed on the body. The treatment had positive results, and the animal was discharged after 58 days.